Asia-Pacific economic cooperation the goods market - Paderanga, Cayetano W., Jr (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1995)
This article looks into the static and dynamic effects of free trade areas such as the ASEAN Free Trade Area (AFTA) and the Asia-Pacific Economic Cooperation (APEC). It emphasizes the political economic role by these groupings in a step-by-step process of opening up and liberalization. It also examines some of the costs of joining APEC and what may be done to ease the process of adjustment.